Learn Single Substance and Mixed Substances With Demonstration Based Videos - Hadiwinata, Simon; Wibawa, I Made Citra (International Journal of Elementary Education, 2021)
This research is motivated by the ineffectiveness and innovation of the teacher to create instructional video media during the pandemic era that uses an online learning model. This study aims to produce demonstration-based learning videos that have been tested for their validity on the topic of single substances and mixed substances in fifth-grade elementary schools. This research is development research carried out using the 4D model with the following stages: (1) define, (2) design, (3) develop, (4) disseminate. The subjects of this study were two material experts, two media experts, and two practitioner experts. At the same time, the object of this research is the development of demonstration-based learning videos on the topic of single substances and mixed substances for fifth-grade elementary school students. This development research using qualitative and quantitative descriptive analysis methods. The data obtained were then analyzed to determine the validity score of demonstration-based learning videos. The average value of demonstration-based learning videos from material experts was 97.5% in the very good category, from the media experts by 95% with the very good category, and from the practitioners by 87% with the good category. Based on this analysis, it can be said that demonstration-based learning videos developed on the topic of single substances and mixed substances are declared valid and can be used in learning in fifth-grade elementary schools.